MORAL EDUCATION ACCORDING TO IBN MISKAWAYH AND AL-GHAZALI - Abd Mukti; Amroeni Drajat; Mourssi Abbas Mourssi Hassan Kahwash (UIN Sumatera Utara Medan, 2021)
One of the most essential Islamic messages is to instill an excellent character to every human being, according to the guidance of the Prophet Muhammad (peace and blessings of Allah be upon him):